Yield Curve Dynamics and Spillovers in Central and Eastern European Countries - Hoffmaister, Willy (IMF Working Papers; Working Paper ;, 2010)
This paper applies the models used to study yield curve dynamics and spillovers in the U.S. and other countries to Central and Eastern European countries (CEE countries). Using the Diebold, Rudebusch, and Aruoba (2006) dynamic version of the Nelson-Siegel representation of the yield curve, the paper finds that the two-way relationship between macroeconomic and financial variables in the CEE countries is similar to the one in mature economies. However, inflation shocks have very little persistence in the CEE countries, owing to the strong convergence trends in these countries-which tend to re-anchor expectations faster. Increased convergence in policies and market integration over time are associated with a stronger correlation between the levels of the yield curves, while the curves slopes are more driven by idiosyncratic factors. Shifts in the euro yield curve are transmitted both to interest rates and inflation expectations in the CEE countries-and transmission is stronger after 2004.